2017
DOI: 10.1136/gutjnl-2017-313823
|View full text |Cite
|
Sign up to set email alerts
|

Wide-field endoscopic mucosal resection versus endoscopic submucosal dissection for laterally spreading colorectal lesions: a cost-effectiveness analysis

Abstract: NCT02000141.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
55
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(65 citation statements)
references
References 57 publications
1
55
0
2
Order By: Relevance
“…47 In a large Australian study, ESD was modeled to be a costeffective modality if applied selectively for colorectal lesions with low-risk submucosally invasive (T1) cancer. 48 The rationale for this being that ESD could lower overall cost by reducing the number of surgical resections and by potentially eliminating short-term surveillance, thereby reducing the total number of surveillance colonoscopies.…”
Section: Colorectal Endoscopic Submucosal Dissectionmentioning
confidence: 99%
“…47 In a large Australian study, ESD was modeled to be a costeffective modality if applied selectively for colorectal lesions with low-risk submucosally invasive (T1) cancer. 48 The rationale for this being that ESD could lower overall cost by reducing the number of surgical resections and by potentially eliminating short-term surveillance, thereby reducing the total number of surveillance colonoscopies.…”
Section: Colorectal Endoscopic Submucosal Dissectionmentioning
confidence: 99%
“…Even with the advent of endoscopic mucosal resection (EMR) as a safe and effective treatment of such large lesions, the referral rate for surgery remains high [3][4][5]. Cost ana-lyses demonstrated that EMR is cheaper than endoscopic submucosal dissection and surgery [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…This practice shows no signs of abating, 12 despite fervent pleas that EMR by an experienced endoscopist should be the first-line treatment for large LSTs, for reasons of both efficacy and cost. [13][14][15][16] To improve the outcomes in patients with large colorectal polyps, endoscopists in the West would do well to emulate their Japanese colleagues. This would entail sharpening our powers of observation and lesion description, increasing our use of electronic chromoendoscopy, and finding better means to share high-resolution images with colleagues and referral physicians.…”
mentioning
confidence: 99%